Combined break-junction tunneling and STM/STS studies of the -tungsten-type superconductor Nb3Sn below and above Tc. (2015) - Ekino, Toshikazu; Gabovich, Alexander M.; Sakai, Yuta; Sugimotoand, Akira; Akimitsu, Jun
No abstract available